Head-mounted displays or traditional videoconferencing – How the choice of a communication medium affects employee well-being - Philip Gubernator; Yannick Frontzkowski; Sven Hauff; Jörg Felfe (Computers in Human Behavior Reports, 2025)
Spatially distributed workers rely on videoconferencing to collaborate. The use of traditional videoconferencing tools can, however, pose a threat to employee well-being. For example, it can lead to fatigue and is often related to increased social isolation and decreased work engagement. Immersive videoconferencing tools such as head-mounted displays may reduce this threat by increased sociability (i.e. the ability of a tool to facilitate social interaction) and increased perception of co-presence. To test our hypotheses, we conducted an experimental study systematically varying traditional non-immersive 2-D and immersive 3-D videoconferences with N = 124 participants. Our results show a trade-off effect of immersive videoconferencing tools on employee well-being, as they increase relational (group cohesion) and happiness-related well-being (engagement) while decreasing health-related well-being (visual fatigue). In addition, we found a detrimental effect on general fatigue which is, however, outweighed by a positive effect via increased sociability. Furthermore, our results highlight the individual role of sociability and co-presence in shaping these effects as distinct mediators.